Frequency and impact of individual symptoms on quality of life in dry eye disease in patients presenting to a tertiary care hospital - Saba Ali Arif; Muhammad Ifraheem Khan; Muhammad Salman Abid; Ayla Babar; Mohammad Ali Arif; Hafiz Muhammad Jahanzaib; Inayatullah Khan (Journal of the Pakistan Medical Association, 2021)
Objective: To assess the frequency of symptoms and impact on quality of life in individuals with dry eye disease. Methods: The cross-sectional, study was conducted from December 2018 to June 2019 at the outpatient clinic of the Department of Ophthalmology, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, and comprised dry eye disease patients aged at least 13 years with ocular burning sensation, lacrimation, grittiness, photophobia, redness or itching. Tear Film Breakup time <10 sec and / or positive ocular surface staining >5 corneal spots, >9 conjunctival spots, lid margin staining ?2mm in length were used to diagnose the disease. Data was collected using the Dry Eye Quality of Life Score questionnaire. Data was analysed using SPSS 25. Results: of the 191 patients, 135(71%) were females and 56(29%) were males. The overall mean age was 39.8±16.6 years. Itching 155(81.2%), watering 151(79.1%) and burning 124(64.9%) were the most frequent symptoms, with watering (p<0.001) and photophobia (p=0.012) significantly impacting quality of life. Conclusions: The most common symptoms among patients of dry eye disease affecting their quality of life were itching, watering, burning, photophobia and low mood. Key Words: Quality of life in dry eye disease, Dry eye disease, Lacrimation, Photophobia, Continuous...